Answer:
m = -5
Step-by-step explanation:
16−(7m+3)=8(1−m)
16 - 7m - 3 = 8 - 8m
16 - 3 - 8 = 7m - 8m
5 = -m
(-1) * 5 = -m * (-1)
-5 = m
therefore, m = -5
Answer:
Tn = 3n-1
T6 = 17
Step-by-step explanation:
Given the arithmetic sequence;
2, 5...
first term a = 2
Common difference d = 5-2 = 3
nth term of an AP is expressed as Tn = a + (n-1)d
Tn = 2 + (n-1)(3)
Tn = 2 + 3n-3
Tn = 3n-1
Get the 6th term
T6 = 3(6)-1
T6 = 18-1
T6 = 17
Hence the 6th term of the sequence is 17
Let the third angle of the triangle be y.
y + 64° + 45° = 180° (angle sum of triangle is 180°)
x + y = 180° (angle of a straight line is 180°)
Notice that they both equal 180°. This means that they are the same thing, hence:
y + 64° + 45° = x + y
Since y = y, it is not necessary to write them down. Remove y from both sides of the equation:
64° + 45° = x
Surprise! exterior angle = sum of interior opposite angles.
I hope this clears up any confusion you might have. If not, feel free to leave a comment with your question.
Answer:
Step-by-step explanation:
![- \frac{9}{8} = v - \frac{1}{2} \\ \\ \frac{1}{2} - \frac{9}{8} = v \\ \\ \frac{4}{8} - \frac{9}{8} = v \\ \\ \frac{4 - 9}{8} = v \\ \\ v = - \frac{5}{8} \\](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B9%7D%7B8%7D%20%20%3D%20v%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B1%7D%7B2%7D%20%20-%20%20%5Cfrac%7B9%7D%7B8%7D%20%20%3D%20v%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B4%7D%7B8%7D%20%20-%20%20%5Cfrac%7B9%7D%7B8%7D%20%20%3D%20v%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B4%20-%209%7D%7B8%7D%20%20%3D%20v%20%5C%5C%20%20%5C%5C%20v%20%3D%20%20-%20%20%5Cfrac%7B5%7D%7B8%7D%20%20%5C%5C%20)